Bone mineral density, osteoporosis, and fractures among people with eating disorders: a systematic review and meta‐analysis. (13th January 2016) - Solmi, M.; Veronese, N.; Correll, C. U.; Favaro, A.; Santonastaso, P.; Caregaro, L.; Vancampfort, D.; Luchini, C.; De Hert, M.; Stubbs, B.
Abstract : Objective: To provide meta‐analytical evidence of bone mineral density (BMD), fractures, and osteoporosis rates in eating disorders (ED) vs. healthy controls (HCs). Method: Three independent authors searched major electronic databases from inception till August 2015 for cross‐sectional studies reporting BMD in people with ED (anorexia nervosa, (AN); bulimia nervosa, (BN); eating disorders not otherwise specified, (EDNOS)) vs. HCs. Standardized mean differences (SMDs) ±95% and confidence intervals (CIs) were calculated for BMD, and odds ratios (ORs) for osteopenia, osteoporosis, and fractures. Results: Overall, 57 studies were eligible, including 21 607 participants (ED = 6485, HCs = 15 122). Compared to HC, AN subjects had significantly lower BMD values at lumbar spine (SMD = −1.51, 95% CI = −1.75, −1.27, studies = 42), total hip (SMD = −1.56, 95%CI = −1.84, −1.28, studies = 23), intertrochanteric region (SMD = −1.80, 95%CI = −2.46, −1.14, studies = 7), trochanteric region (SMD = −1.05, 95%CI = −1.44, −0.66, studies = 7), and femoral neck (SMD = −0.98, 95%CI = −1.12, −0.77, studies = 20). Reduced BMD was moderated by ED illness duration and amenorrhea ( P < 0.05). AN was associated with an increased likelihood of osteoporosis (OR = 12.59, 95%CI = 3.30–47.9, P < 0.001, studies = 4) and fractures (OR = 1.84, 95% CI = 1.17–2.89, I 2 = 56, studies = 6). No difference in BMD was found between BN and EDNOS vs. HC. Conclusion: People with AN have reduced BMD, increased odds of osteoporosis and risk of fractures. Proactive monitoring and interventions are required to ameliorate bone loss in AN.